DAMPAK PANDEMI COVID-19 TERHADAP KEPUTUSAN ORANG TUA MELAKUKAN IMUNISASI RUTIN ANAK: LITERATURE REVIEW - Allisa Amelia Santoso; Tri Yunis Miko Wahyono (J-KESMAS: Jurnal Kesehatan Masyarakat, 2022)
The COVID-19 pandemic has affected to health care system including routine childhood immunization services globally. According to official data published by WHO and UNICEF, 23 million children missed out on basic routine immunization services and up to 17 million children did not receive a single vaccine in 2020. The objective of this study is to provide an overview of the impact of the COVID-19 pandemic on parental decisions to carry out routine immunization. The design used is a literature review with an electronic search using Elsevier, Google Scholar, and PubMed published between 2020-2022. Inclusion criteria for this study were primary studies, parents with children under 24 months of age, open-access journals written in English and Indonesia. Four journals that met the inclusion criteria found that the fear of COVID-19 infection was a major factor for parents who had delayed their children's routine immunization. Socioeconomic factors and the availability of accurate information about immunization affect parental decisions to immunize their children during the COVID-19 pandemic.